STUDENTS’ PREFERENCES ON ONLINE LEARNING IN THE NEW NORMAL PERIOD OF THE COVID-19 PANDEMIC - Roswani Siregar; Syahron Lubis; Risnawaty Risnawaty; Andri Ramadhan (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
This study aims to investigate the students' preferences on online learning systems in the new normal period of the Covid-19 pandemic. This study used descriptive qualitative research and adopted a survey method to collect the quantitative data from 95 students in two universities related to students experiences on learning classes, devices and mediums, learning environment, material format and comprehension, resources, time management, peers and lecturer communication, and limitation and benefit of online learning. This study also highlights the lecturer's effort to overcome the general obstacles amid the online learning process. The use of various formats of learning materials is effective for students who face poor internet access in remote areas. Moreover, feedback is vital for both lecturer and students in maintaining the engagement of communication. Finally, the results of this study provide essential information in understanding the effectiveness of online learning particularly amid the new normal period from the university setting.